BODY MORPHOMETRY AND BODY CONDITION SCORE AS INDICATORS OF NUTRITIONAL STATUS IN CATTLE: LITERATURE REVIEW - Wardana, Rr. Allamanda Ardia; Heryani, Luh Gde Sri Surya; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2026)
Evaluating the nutritional status of cattle is important for supporting productivity, reproductive efficiency, and health. Body morphometry and body condition score (BCS) are widely used methods because they are practical and can directly describe the physiological conditions of cattle. This review analyzed the role of body morphometry and BCS in determining the nutritional status of cattle and their relationship with production and reproductive performances. We used a systematic literature review method by searching scientific articles from the ScienceDirect, PubMed, Google Scholar, Garuda, and DOAJ databases published between 2016 and 2026. Article selection was performed using the PICO approach and PRISMA guidelines to obtain relevant open-access studies. The review showed that chest girth is the most representative morphometric parameter for predicting body weight, production capacity, and nutritional status because of its close relationship with muscle development and fat deposition in the thorax. Body length and withers height also reflect skeletal capacity and growth performance. BCS represents energy reserves and metabolic conditions associated with reproductive efficiency. The combination of morphometry and BCS provides a more comprehensive nutritional evaluation than either method alone. Body morphometry and BCS can be used as objective, economical, and applicable approaches for monitoring the nutritional status of cattle, especially in smallholder farming systems. Future studies should develop breed-based morphometric standards and digital technologies to improve the accuracy of nutritional assessment in cattle.